Thermochemical Conversion of Oily Sludge, Composition, Hazards, and Treatment Strategies: An Overview - Mahmod A. Abdulqader (AUIQ Complementary Biological System)
Oily sludge (OS) is considered one of the most complex by-products produced in the petroleum industry as an unwanted. This work aims to provide a comprehensive review focused on the dangers of stockpiled OS, its sources and contents, as well as its complex composition. This study also analyzes the global annual generation and stockpiling quantities of OS. Therefore, the thermochemical conversion, hydrothermal carbonization (HTC) char produced via HTC called hydrochar, pyrolysis (PY) char produced via PY named pyro-char, and microwave (MW) processes, while the char produced MW labeled micro-char. In conclusion, this study will facilitate researchers and provide a clear understanding of OS making it easy to recovered oil, convert, or exploit as fuel, absorbent materials, or fertilizer for soil. Therefore, this research will contribute to preserving the environment and preserving the planet.